2017
DOI: 10.3847/2041-8213/aa70ed
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the Hα-emitting Region in the Wind of η Carinae

Abstract: The massive evolved star η Carinae is the most luminous star in the Milky Way and has the highest steady wind mass-loss rate of any known star. Radiative transfer models of the spectrum by Hillier et al. predict that Hα is mostly emitted in regions of the wind at radii of 6-60 AU from the star (2.5-25 mas at 2.35 kpc). We present diffraction-limited images (FWHM ∼ 25 mas) with Magellan adaptive optics (MagAO) in two epochs, showing that η Carinae consistently appears ∼2.5-3 mas wider in Hα emission compared to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The primary star is an LBV with an extremely powerful wind: a mass-loss rate of 8.5×10 −4 M yr −1 and terminal wind velocity of 420 km s −1 Groh et al 2012a;Clementel et al 2015a). Under these conditions, showed that H-alpha could be formed in an extended region between 6 − 60 AU (assuming R * = 60 R ) outwards from the primary, and these results have been observationally supported by Wu et al (2017). As a result, we know the primary star displays spectral lines formed in highly extended regions from the central star.…”
Section: η Carinae: the Extreme Casementioning
confidence: 68%
“…The primary star is an LBV with an extremely powerful wind: a mass-loss rate of 8.5×10 −4 M yr −1 and terminal wind velocity of 420 km s −1 Groh et al 2012a;Clementel et al 2015a). Under these conditions, showed that H-alpha could be formed in an extended region between 6 − 60 AU (assuming R * = 60 R ) outwards from the primary, and these results have been observationally supported by Wu et al (2017). As a result, we know the primary star displays spectral lines formed in highly extended regions from the central star.…”
Section: η Carinae: the Extreme Casementioning
confidence: 68%
“…6), though the difference is marginal compared with the Hα and continuum observations of η Carinae. 35 This feature represents either of the expected astrophysical feature-limb brightening of the shock feature at Hα-or the difference of PSFs at wavelengths between the Hα and the continuum filters. To further test whether our data reduction can be affected by an artifact (e.g.…”
Section: Resultsmentioning
confidence: 99%